THE ADAPTATION OF MYTHOLOGICAL CHARACTERS ON THE MECHANICS AND NARRATIVES OF THE HEROES IN MOBILE LEGENDS: BANG BANG - Majid Hidayaturrohim (CrossOver, 2021)
Recently video games have become a professional sport and a source of livelihood with the new sport, electronic sports (E-sport). E-sport is also held on several devices such as on PCs and smartphones. The video game itself can be seen as literature because players often encounter characters, mechanics and, storylines in a game. Yet the story and the characters in a game are presented differently. The characters in the game studied in this article are adapted from mythology from several regions into Mobile Legends: Bang Bang. Therefore, this research aims to describe the adaptation of characters from the mythology of several regions into Mobile Legends: Bang Bang in terms of appearance, mechanics, and narrative. In this research, researcher used descriptive qualitative method to explain the differences. The data collection technique used by the researcher is literary analysis. The result of this research shows that twenty characters have similarities with mythology until the end of 2020. Generally, these twenty characters are divided into four races, namely gods, humans, elves, and giants. Meanwhile, dominant characters adapted are of the elf race with ten characters who are told from Nordic mythology. This research concludes that the character adaptations performed by video games are not completely equated with the appearance, narrative, and abilities of the original mythology. This is consistent with Hutcheon's adaptation theory in the Interacting - Telling or Showing section. Thus, the adapter does not completely take it from mythology but only interprets it as a character in a video game that interacts with the player.